Acute small-bowel toxicity during neoadjuvant combined radiochemotherapy in locally advanced rectal cancer: determination of optimal dose-volume cut-off value predicting grade 2-3 diarrhoea - Reis, Tina; Welzel, Grit; Wenz, Frederik; Hofheinz, Ralf-Dieter; Mai, Sabine (Radiation oncology, 2015)
Background: Current therapeutic standard for locally advanced rectal cancer is the neoadjuvant radiochemotherapy with total mesorectal excision. Diarrhoea is the main acute side effect, induced by the dose to the small-bowel, frequently leading to a treatment modification. Aim of this study was to analyse the differences between the irradiated small-bowel volumes and the occurrence of acute diarrhea during combined radiochemotherapy for rectal cancer.Current therapeutic standard for locally advanced rectal cancer is the neoadjuvant radiochemotherapy with total mesorectal excision. Diarrhoea is the main acute side effect, induced by the dose to the small-bowel, frequently leading to a treatment modification. Aim of this study was to analyse the differences between the irradiated small-bowel volumes and the occurrence of acute diarrhea during combined radiochemotherapy for rectal cancer. Methods: 45 patients treated with a neoadjuvant radiochemotherapy (three-field box 50.4 Gy; Cetuximab, Capecitabine, Irinotecan) for locally advanced rectal cancer within a prospective phase I/II study were evaluated. Based on the dose-volume histograms, the small-bowel volumes receiving doses of 5, 10 … 45 Gy (V5, V10 …V45) were calculated and compared with the prospectively documented small- bowel toxicities. Results: There was a statistically significant difference between irradiated small-bowel volumes and the severity of therapy related diarrhoea. The strongest validity concerning the risk of developing a grade 2–3 diarrhoea was seen at a dose level of 5 Gy (V 5) with a small-bowel volume of 291.94 cc. Patients with V 5 > 291.94 cc had significantly more often grade 2–3 diarrhoea, than patients with V5 below this cut-off value (82% vs. 29%; p < 0.0001). Conclusions: In the inverse treatment planning of rectal caner patients the small-bowel volume receiving 5 Gy should be limited to about 300 cc.
Gesehen am: 14.08.2017